Placebo Rates in Randomized Controlled Trials of Proctitis Therapy: A Systematic Review and Meta-Analysis Placebo Response in Proctitis. (5th August 2022) - De Silva, Theshani A; Alphonsus, Lotus; Ma, Christopher; Hogan, Malcolm; Sedano, Rocio; Narula, Neeraj; Danese, Silvio; Peyrin-Biroulet, Laurent; MacDonald, John K; Singh, Siddharth; Jairath, Vipul
Abstract: Background and Aims: Treatment options for proctitis are limited. To assist trial design for novel therapeutics, we conducted a systematic review and meta-analysis of proctitis randomized controlled trials [RCTs] to quantify placebo rates and identify factors influencing them. Methods: We searched MEDLINE, EMBASE and CENTRAL from inception to June 2021. Placebo-controlled trials of pharmacological interventions for proctitis were eligible. Placebo clinical response and remission rates for induction and maintenance trials were extracted and pooled using a random-effects model. Mixed-effects meta-regression was used to evaluate the impact of patient and study-level characteristics. Results: Twenty RCTs [17 induction and four maintenance phases] were included. The most common intervention was aminosalicylates and most studies investigated topical medications. The pooled placebo clinical response and remission rates for induction trials were 28% (95% confidence interval [CI] 22–35%; n  = 17) and 20% [95% CI 12–32%; n  = 9], respectively. Pooled placebo endoscopic response and remission rates were 32% [95% CI 26–39%, n  = 12] and 18% [95% CI 9–33%, n  = 6], respectively. For maintenance trials, the pooled placebo clinical remission rate was 29% [95% CI 16–46%, n  = 17]. Trials published after 2005 and trials with a longer duration of follow-up were associated with significantly lower placebo response rates. Nineteen of 20 studies were assessed as having an unclear risk of bias, reflecting the historical nature of trials. Conclusions: Placebo response and remission rates in proctitis trials are influenced by trial phase and the endpoint being assessed. These contemporary rates will inform trial design for novel therapeutics for treatment of proctitis, which is a large unmet need.